Metagenomic insights into microbial diversity and potential pathogenic transmission in poultry farm environments of Bangladesh - Afroja Yasmin; M. Shaminur Rahman; S. M. Kador; Md. Mustak Ahmed; Md. Eashanul Karim Moon; Humaira Akhter; Munawar Sultana; Anowara Begum (BMC Microbiology)
Abstract The microbiome plays a critical role in poultry health and productivity, influencing growth, immunity, and the overall farm ecosystem. This study investigated microbial diversity, antibiotic resistance pathways, and functional potential across various components of poultry ecosystems—cloacal swabs, droppings, feed, hand swabs, soil, and water—in different districts of Bangladesh. Using 16S rRNA gene amplicon sequencing, we identified 2,745 Operational Taxonomic Units (OTUs) and analyzed microbial richness, community structure, and functional pathways. Alpha diversity metrics revealed that droppings exhibited the highest microbial richness (726 OTUs in Noakhali), while feed samples showed the lowest diversity (211 OTUs). Beta diversity analysis indicated significant differences in microbial composition across sample sources, with PERMANOVA confirming that sample origin accounted for 51.45% of the variability (p < 0.001). Proteobacteria dominated the microbial communities (48.36%), followed by Firmicutes (19.83%) and Cyanobacteria (12.02%). Key genera of concern, such as Enterobacter (26.62% in hand swabs), Acinetobacter (30.87% in cloacal swabs), and Shigella (22.89% in cloacal swabs), were identified, highlighting potential contamination and zoonotic risks. Conversely, beneficial genera like Lactobacillus (36.89% in feed) and Enterococcus (10.78% in droppings) were prevalent, suggesting roles in gut health and nutrient cycling. Functional pathway analysis (KEGG) revealed that carbohydrate and amino acid metabolism were highly active in droppings and feed, reflecting nutrient utilization. Antimicrobial resistance (AMR) pathways, such as 23S rRNA-methyltransferase and multidrug efflux pumps, were widespread, with pathogenic genera (Enterobacter, Acinetobacter, Shigella, Pseudomonas) showing strong positive correlations with AMR pathways. These findings underscore the influence of environmental factors on microbial diversity and functional potential in poultry farming. The study highlights the need for improved management practices and biosecurity measures to mitigate risks associated with microbial pathogens and antimicrobial resistance, ultimately supporting healthier and more sustainable poultry production in Bangladesh.